(How) Does 360-degree feedback benefit the field of entrepreneurship?. (6th June 2018) - Miao, Chao; Humphrey, Ronald H.; Qian, Shanshan; Oh, In-Sue
Abstract : Purpose: Most of the studies in entrepreneurship depend on single-source rating methods to collect data on both predictors and criteria. The threat to effect sizes as a result of using single-source ratings is particularly relevant to psychology-based entrepreneurship research. Therefore, the purpose of this paper is to explore the prospects of applying 360-degree feedback to the field of entrepreneurship and to discuss a set of cases regarding how 360-degree feedback may boost effect sizes in entrepreneurship research. Design/methodology/approach: A qualitative review of current literature was performed. Findings: The review indicated that the effect sizes in psychology-based entrepreneurship research are mostly small and the use of single-source ratings is prevalent; some preliminary findings supported the utility of 360-degree feedback in entrepreneurship research; entrepreneurial orientation (EO) research may benefit from 360-degree feedback; and members of top management teams, employees from research and product development, sales agents, retail buying agents, store sales clerks, and consumers are all valid informants to provide ratings of EO. Originality/value: The present study provided theoretical explanations and used empirical evidence to elucidate how 360-degree feedback may benefit the field of entrepreneurship. In addition, recommendations for future research using 360-degree feedback in entrepreneurship research were offered and discussed. A sample research study on EO using 360-degree feedback was delineated.